Double blind randomised placebo controlled trial of adjunctive prednisolone in the treatment of effusive tuberculous pericarditis in HIV seropositive patients. Issue 2 (1st August 2000) - Hakim, J G; Ternouth, I; Mushangi, E; Siziya, S; Robertson, V; Malin, A
Abstract : OBJECTIVE: To determine the effect of adjunctive prednisolone on morbidity, pericardial fluid resolution, and mortality in HIV seropositive patients with effusive tuberculous pericarditis. DESIGN: Double blind randomised placebo controlled trial. SETTING: Two medical school affiliated referral hospitals in Harare, Zimbabwe. PATIENTS: 58 HIV seropositive patients aged 18–55 years with tuberculous pericarditis. INTERVENTIONS: All patients received standard short course antituberculous chemotherapy and were randomly assigned to receive prednisolone or placebo for six weeks. MAIN OUTCOME MEASURES: Clinical improvement, echocardiographic and radiologic pericardial fluid resolution, and death. RESULTS: 29 patients were assigned to prednisolone and 29 to placebo. After 18 months of follow up there were five deaths in the prednisolone treated group and 10 deaths in the placebo group. Mortality was significantly lower in the prednisolone group (log rank χ 2  = 8.19, df = 1, p = 0.004). Resolution of raised jugular venous pressure (p = 0.017), hepatomegaly (p = 0.007), and ascites (p = 0.015), and improvement in physical activity (p = 0.02), were significantly more rapid in the prednisolone treated patients. However, there was no difference in the rate of radiologic and echocardiographic resolution of pericardial effusion. CONCLUSIONS: Adjunctive prednisolone for effusive tuberculous pericarditis produced a pronounced reduction in mortality. It is suggested prednisolone should be added to standard short course chemotherapy to treat HIV related effusive tuberculous pericarditis.